2011
DOI: 10.1093/ejechocard/jer139
|View full text |Cite
|
Sign up to set email alerts
|

Altered two-dimensional strain measures of the right ventricle in patients with Brugada syndrome and arrhythmogenic right ventricular dysplasia/cardiomyopathy

Abstract: By 2D strain technique it is possible to observe mild abnormalities in RV systolic and diastolic function of BrS patients that are less pronounced than those observed in ARVD/C patients. These results help to better define the phenotypic characteristics of BrS patients and represent the basis for future studies aimed at testing their clinical usefulness in BrS patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…The present study supports previous findings of RV involvement in BS [8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]38]. Besides known structural RV abnormalities [15,[17][18][19] (Table 2), our data demonstrated delays in the right (RVED) and the interventricular (IVED) conduction (Fig.…”
Section: Rv Ejection Delaysupporting
confidence: 92%
See 1 more Smart Citation
“…The present study supports previous findings of RV involvement in BS [8,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]38]. Besides known structural RV abnormalities [15,[17][18][19] (Table 2), our data demonstrated delays in the right (RVED) and the interventricular (IVED) conduction (Fig.…”
Section: Rv Ejection Delaysupporting
confidence: 92%
“…However, subtle structural abnormalities, particularly in the right ventricle (RV) and the right ventricular outflow tract (RVOT) have been identified on computed tomography (CT) [15,16], cardiac magnetic resonance (CMR) [17][18][19], echocardiography [20][21][22] and biopsies [23,24]. Furthermore, studies confirmed that BS is a RV disease and consented that the anterior RVOT epicardium is likely to be the primary arrhythmogenic area in BS [8,9,[25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…6 Patients with Brugada syndrome and arrhythmogenic RV cardiomyopathy have differential RV involvement, with the basal and mid segments more affected than the apex. 25 Similarly, we observed relative sparing of RV apical function with age. An increase in apical segmental contribution to total strain was observed in older subjects and may be a ''compensatory'' mechanism to adjust for the reductions in basal and mid segmental function.…”
Section: Rv Systolic Functionsupporting
confidence: 70%
“…Furthermore, they did not find any differences in RV dimensions and ejection fraction (EF) between BrS patients and healthy controls [10]. Interestingly, using the two-dimensional strain technique, mild RV function abnormalities were observed in BrS patients [11].…”
Section: Utility Of Cardiac Imaging In Brsmentioning
confidence: 93%